Discrimination of COVID‐19 From Inflammation‐Induced Cytokine Storm Syndromes Using Disease‐Related Blood Biomarkers. Issue 10 (3rd September 2021) - Kessel, Christoph; Vollenberg, Richard; Masjosthusmann, Katja; Hinze, Claas; Wittkowski, Helmut; Debaugnies, France; Nagant, Carole; Corazza, Francis; Vély, Frédéric; Kaplanski, Gilles; Girard‐Guyonvarc'h, Charlotte; Gabay, Cem; et al.
Abstract : Objective: Infection with the novel coronavirus SARS–CoV‐2 triggers severe illness with high mortality in a subgroup of patients. Such a critical course of COVID‐19 is thought to be associated with the development of cytokine storm, a condition seen in macrophage activation syndrome (MAS) and secondary hemophagocytic lymphohistiocytosis (HLH). However, specific data demonstrating a clear association of cytokine storm with severe COVID‐19 are still lacking. The aim of this study was to directly address whether immune activation in COVID‐19 does indeed mimic the conditions found in these classic cytokine storm syndromes. Methods: Levels of 22 biomarkers were quantified in serum samples from patients with COVID‐19 (n = 30 patients, n = 83 longitudinal samples in total), patients with secondary HLH/MAS (n = 50), and healthy controls (n = 9). Measurements were performed using bead array assays and single‐marker enzyme‐linked immunosorbent assay. Serum biomarker levels were assessed for correlations with disease outcome. Results: In patients with secondary HLH/MAS, we observed pronounced activation of the interleukin‐18 (IL‐18)–interferon‐γ axis, increased serum levels of IL‐1 receptor antagonist, intercellular adhesion molecule 1, and IL‐8, and strongly reduced levels of soluble Fas ligand in the course of SARS–CoV‐2 infection. These observations appeared to discriminate immune dysregulation in critical COVID‐19 from the well‐recognized characteristics of other cytokine storm syndromes. Conclusion: Serum biomarker profiles clearly separate COVID‐19 from MAS or secondary HLH in terms of distinguishing the severe systemic hyperinflammation that occurs following SARS–CoV‐2 infection. These findings could be useful in determining the efficacy of drugs targeting key molecules and pathways specifically associated with systemic cytokine storm conditions in the treatment of COVID‐19.